Solidarity Economy Networks: the Case of Brazil - Castilla Carrascal, Ivette Tatiana (Cooperativismo & Desarrollo, 2014)
This article presents reflections (resulting from a Master’s dissertation in sociology) about diverse contributions by the solidarity economy networks in the construction of a solidarity market in Brazil. The first part of the article is a discussion about the different characteristics of the networks in terms of more general social theories, such as networks in the field of the solidarity economy. The second part briefly characterizes the Redes Bodega, acs Amazonia, Rede Ecovida, Central do Cerrado and Justa Trama networks, showing their fair trade and solidarity trade practices, history and the actors involved. Finally, the considerations present certain challenges faced by the networks, along with impacts that the actors in the networks experience within them.